Malawi : Second and Third Reviews Under the Three-Year Extended Credit Facility Arrangement and Requests for Waivers of Nonobservance of Performance Criteria and Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Malawi's Second and Third Reviews Under the Three-Year Extended Credit Facility Arrangement and Requests for Waivers of NonObservance of Performance Criteria and Augmentation of Access. Program-supported structural reforms advanced, addressing several important gaps that had previously been identified in public financial management. All quantitative performance criteria were met except those on the primary balance, which were missed largely due to faster than envisaged implementation of rural electrification and development projects, unexpected spending for disaster relief and to ensure safety during elections and post-election protests. The authorities aim to entrench macroeconomic stability, preserve debt sustainability, and advance governance reforms while attaining higher, more inclusive, and resilient growth. Essential reconstruction and security spending will be accommodated by reprioritizing spending and a modest relaxation in the FY 2019/20 domestic primary balance target. Monetary policy remains targeted on containing inflation and exchange rate flexibility will buffer shocks and preserve competitiveness. Financial sector resilience continues to be strengthened.